Polynomial coefficients based off of its roots

Algebra Level 3

If the ordered triple (a, b, c) of integers are the coefficients for x 3 + a x 2 + b x + c = 0 x^3+ax^2+bx+c=0 . Find the minimum of a + b + c |a+b+c| If x = 2 + 3 3 + 2 3 3 x=\sqrt[3]{2+\sqrt{3}}+\sqrt[3]{2-\sqrt{3}}

6 5 7 8

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Brandon Zhang
Jul 29, 2015

When we look at x = 2 + 3 3 + 2 3 3 x=\sqrt[3]{2+\sqrt{3}}+\sqrt[3]{2-\sqrt{3}} , we don't like the cube roots sitting there. That gives us the idea to cube both sides.

Cubing, we get:

x 3 = 2 + 3 + 2 3 + 3 ( ( 2 + 3 ) 2 ( 2 3 ) 3 + ( 2 + 3 ) ( 2 3 ) 2 3 ) x^3=2+\sqrt{3}+2-\sqrt{3}+3(\sqrt[3]{(2+\sqrt{3})^2(2-\sqrt{3})}+\sqrt[3]{(2+\sqrt{3})(2-\sqrt{3})^2})

When we look at those ugly radicals, we see difference of squares: ( 2 + 3 ) ( 2 3 ) = 1 (2+\sqrt{3})(2-\sqrt{3})=1 which means those ugly radicals become:

3 ( 2 + 3 3 + 2 3 3 ) 3(\sqrt[3]{2+\sqrt{3}}+\sqrt[3]{2-\sqrt{3}})

But we already know x = 2 + 3 3 + 2 3 3 x=\sqrt[3]{2+\sqrt{3}}+\sqrt[3]{2-\sqrt{3}} so the equation becomes: x 3 = 4 + 3 x x^3=4+3x

Putting into standard form and finding the absolute value of the sum of the coefficients, we get 7 \boxed{7}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...